2015
DOI: 10.1016/j.ijid.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in impact of maternal milk on vertical transmission between Hepatitis B virus and Human cytomegalovirus

Abstract: Breastfeeding is not a risk factor for maternal-to-infant transmission of HBV after the recommended prophylaxis is implemented. However, viral DNA positive breast milk is a main source for vertical transmission of HCMV to infants who are not protected by a standard immunoprophylaxis protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In infants and children, HBV is largely acquired by VT. If exposed to HBV, neonates have a 90% risk of acquiring chronic HBV infection, whereas adults have a 5–10% chance of developing chronic infection 1,3,6. This vast contrast speaks to the differences in immune response observed in children versus adults.…”
Section: Hbvmentioning
confidence: 99%
See 2 more Smart Citations
“…In infants and children, HBV is largely acquired by VT. If exposed to HBV, neonates have a 90% risk of acquiring chronic HBV infection, whereas adults have a 5–10% chance of developing chronic infection 1,3,6. This vast contrast speaks to the differences in immune response observed in children versus adults.…”
Section: Hbvmentioning
confidence: 99%
“…Although HBV DNA and HBsAg can be detected in breast milk,3,4,9 no study to date has demonstrated a statistically significant increase in VT in infants breastfed by HBV-positive mothers 3,9. Therefore, HBV-positive mothers should not be advised against breastfeeding.…”
Section: Hbvmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Clinical and epidemiological studies have shown that individuals getting HBV infection vertically are at a higher risk of developing detrimental complications of the liver and progression towards chronic or in cases HCC. 14,[23][24][25] There is no specific non-invasive biomarker for predicting MTCT of HBV. Moreover, the depressed immune response during pregnancy also plays an important role in manifestation HBV in mother and foetal health during birth.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding is the most common route of CMV transmission from seropositive mothers to their babies postnatally (1)(2)(3)(4). Most CMV seropositive mothers become reactivated during lactation up to 96% and excrete the virus in breast milk without clinical or laboratory signs of systemic infection (5)(6)(7)(8)(9)(10)(11)(12)(13). CMV transmission rate through breast milk is 58%-69% in term infants, 5.7%-58.6% in preterm infants, and 38% in preterm infants with birth weights of <1,500 g or GA <32 weeks (2,8,14,15).…”
Section: Introductionmentioning
confidence: 99%